FALSE DIAGNOSIS IS A THREAT - A CASE STUDY - RP, JAYASWAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: To explore the possibility of false diagnosis and threat to health. Methods: In the present study, a case history of 23-year–old lactating woman was taken. Seventy-two test parameters were examined at SRL Lab Gurugram and Thyrocare Mumbai on alternative days from different location under variable climatic and family environment. Results: The tests report of SRL lab was abnormal in range in compare to the reports of Thyrocare Lab. Conclusion: The present study is expected to attract the attention of people who may be in the position of acquiring health services. In such approach, incidence of false-positive laboratory reports either due to technical errors or patient own conditions is thought to misguide a clinician who may prescribe wrong medicines to the patient. This type of mistake may invite unwanted and life-threatening threats to the patients’ body if inappropriate or wrong drugs are given to the patient. Through this study, it is now suggested to be cautious and should verify before taking any drugs suggested by clinicians. Once a diagnosis is confirmed and considered repeatedly, the development of adverse health effects due to unwanted drugs can be minimized. Keywords: Diagnosis, Treatment, Drugs, Laboratory reports.